ORGANIZATION OF DISTANCE LEARNING FOR HUMANITIES STUDENTS USING GOOGLE CLASSROOM - Galizina; Palanchuk; Afonin; Krivova; Lyapunova (Revista Inclusiones, 2020)
Over the past decades, there has been a process of intensive introduction of distance learning innovations into the traditional education system based on modern information and communication technologies and their harmonious combination. This became possible primarily due to the development of the Internet, which made it possible to transmit the required amount of data at any distance, to hold online discussions freely with other Internet users and to post the necessary messages on the websites, making them accessible to everyone. The article presents the peculiarities of handling Google Classroom in distance learning. According to the results of the pedagogical experiment in the use of Google Classroom in the educational process of Humanities students, it was concluded that the use of this system in the educational process contributes to the improvement of the academic achievements of Humanities students.